Grasslands Grown : Creating Place on the U.S. Northern Plains and Canadian Prairies - Rozum, Molly Patrick (Book collections on Project MUSE., 2021)
"An exploration of modern regionalism and senses of place developing among generations of settler colonial society on North America's northern grasslands"--